ECONOMIC MECHANISM OF FUNCTIONING OF THE PRODUCTION SYSTEM BASED ON THE USE OF LEAN TECHNOLOGIES - Chistnikova, Irina; Antonova, Marina; Serova, Elizaveta; Skliarenko, Igor; Alekhina, Elena (Revista Inclusiones, 2020)
The article is devoted to the study and formalization of the economic mechanism of production systems that use lean technologies. Based on the generalization of scientific theories, the content of the economic mechanism of production systems as a specific process of production and economic activity, organized with the principles in mind, is formulated. The key features and management aspects of the economic mechanism of the production system functioning based on lean technologies are identified.